(3EOGQI efXheGJ GdJShjb GdYQHj hGdOhdj (B/s - (3GdfLGQ, aQjOs ((3GdEScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2004)
(3GdJShjb hGdCgOGa GdbhejI(B- (3GdJShjb eaJGM GdJbOje(B- (3GdJShjb hGdJfejI GdeJhGRfI(B- (3GdSdhc GdJShjbj(B- (3LOGhd GdCgOGa GdJShjbjI(B- (3JUeje fXe GdJShjb(B- (3GdJNWjW GdJShjbj(B- (3GdESJQGJjLjI GdYGeI ddJShjb(B- (3fXGe GdeYdheGJ hGdHMhK GdJShjbjI(B- (3HfGA THcI bfhGJ GdJhRjY(B- (3EOGQI GdfXe GdJShjbjIs
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdJShjb GdYQHjs